Mapping Community Engagement: The Co-Design of Union Square Plaza. - Abdul Majid, Moiz.; Duong, Tony.; Huber, Sarah Jane.; Monroe, Marquez.; Piasecki, Kathryn. (Tufts University. Tisch Library., 2023)
2022 M.A./M.S. in Urban and Environmental Policy and Planning Field Project. Client: Design Studio for Social Intervention (DS4SI)